2018
DOI: 10.1038/s41467-018-06569-4
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic association between olfactory identification and spatial memory in humans

Abstract: It was recently proposed that olfaction evolved to aid navigation. Consistent with this hypothesis, olfactory identification and spatial memory are linked to overlapping brain areas which include the orbitofrontal cortex and hippocampus. However, the relationship between these two processes has never been specifically investigated. Here, we show that olfactory identification covaries with spatial memory in humans. We also found that the cortical thickness of the left medial orbitofrontal cortex, and the volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 63 publications
11
59
0
Order By: Relevance
“…It is also possible that the over-engagement of the stimulus-response learning system, through the use of GPS, exerts negative effects on spatial memory due to the competitive nature of the two systems. Several studies have shown, for example, that lesioning the hippocampus or other structures that are part of the neural circuit mediating spatial memory results in impaired spatial memory but facilitates stimulus-response learning 15,18,25,49 . Repeatedly and habitually tapping into the stimulus-response learning system may likewise hinder spatial memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the over-engagement of the stimulus-response learning system, through the use of GPS, exerts negative effects on spatial memory due to the competitive nature of the two systems. Several studies have shown, for example, that lesioning the hippocampus or other structures that are part of the neural circuit mediating spatial memory results in impaired spatial memory but facilitates stimulus-response learning 15,18,25,49 . Repeatedly and habitually tapping into the stimulus-response learning system may likewise hinder spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…Our tasks allow us to measure several facets of navigation, including the extent of navigation strategy use (people can use the same strategy but rely on it to different extents), learning (how quickly people learn about a new environment), cognitive mapping, landmark encoding and reliance, and flexibility/rigidity. The spatial memory and stimulus-response strategies are distinct as they rely on separate neural networks and demonstrate a double dissociation, in that lesioning the spatial memory neural circuit impairs spatial memory but spares stimulus-response learning, while lesioning the stimulus-response neural circuit impairs stimulus-response learning but spares spatial memory 11,15,[18][19][20][21][22][23][24][25] . Thus, navigation is a broad process that includes two distinct methods: spatial learning and memory and stimulus-response learning and memory.…”
Section: Habitual Use Of Gps Negatively Impacts Spatial Memory Duringmentioning
confidence: 99%
“…However, research on human olfaction has rarely been addressed in spatial cognition research. A few exceptions are the studies by Dahmani et al (2018) showing that olfactory identification covaries with spatial memory on the behavioral and neural level. Jacobs, Arter, Cook, and Sulloway (2015) demonstrated that humans are capable of returning to a previously learned spatial location based on an olfactory cue.…”
Section: Olfactory Cues In Landmark-based Wayfindingmentioning
confidence: 99%
“…Landmark‐based wayfinding with odors has repeatedly been demonstrated in the animal kingdom, mainly for species such as desert ants (e.g., Steck, ; Steck, Hansson, & Knaden, , ) and rats (e.g., Rossier & Schenk, ). For humans it has recently been proposed that—besides the classical functions of the olfactory system (e.g., Stevenson & Attuquayefio, )—olfaction developed to aid spatial orientation and navigation (Dahmani et al, ). This approach has been termed the olfactory spatial hypothesis (Jacobs, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finding novel resources is key to animals foraging in dynamic environments, such as tropical rainforests. Individuals can improve the localization of new resources via specialized behaviours, such as specific movement or search strategies (Humphries et al 2012) or increased sensitivity to certain environmental cues (Dahmani et al 2018). Such strategies might differ between the sexes (Croft et al 2003a), but are unlikely to explain our findings.…”
Section: Discussionmentioning
confidence: 75%